A RARE AND UNUSUAL CAUSE OF DISCHARGING SINUS AROUND THE KNEE - Kamath, Surendra Umesh; Kamath, Dr Shaila S; Tejaswi, Purnachandra (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT A 56-year-old male presented to our outpatient department with a history of discharging sinus over the medial aspect of right knee since 6 months. He had a history of road traffic accident with a crush injury to right knee 17 years ago for which he was treated by vascular, plastic, and orthopedic surgeons with hospitalization for about 3 months. Imaging studies with clinical examination suggested a possible diagnosis of chronic osteomyelitis distal femur right with a sequestrum. On exploration, the sinus tract was leading to cavity in the posterior aspect femur containing pus and 4 cm long vascular graft material. Possibly the vascular graft was used for the treatment of vascular injury 17 years ago was the cause for persistent sinus. Keywords: Persistent sinus, Sinus exploration, Vascular graft.